Words That Matter: Native Language Use, Mindfulness, and Their Impact on Tourist Satisfaction - Tamanine, Reda; Baazizi, Yassine; Houssas, M’barek; Ahachmi, Mustapha; Bennoudi, Hanane (LACULTOUR: Journal of Language and Cultural Tourism, 2025)
This study investigates the combined effects of residents’ use of native languages and tourists’ mindfulness on perceived authenticity and overall satisfaction in multilingual tourism destinations. Using a sample of 281 tourists, data were collected via a structured survey. Structural Equation Modeling (SEM) evaluated the hypothesized relationships. The findings reveal that residents’ use of native languages significantly enhances tourists’ perceptions of authenticity, which, in turn, positively impacts satisfaction. Furthermore, mindfulness moderates the effects of native language use on perceived authenticity, highlighting its role in shaping authentic experiences. These results underscore the importance of cultural preservation through native language use in fostering meaningful and satisfying tourist experiences. This study provides actionable insights for tourism stakeholders, emphasizing the balance between cultural authenticity and tourist engagement to enhance destination competitiveness.